The earliest example of sexual dimorphism in bivalves—evidence from the astartid Nicaniella (Lower Jurassic, southern Germany). (November 2021) - Karapunar, Baran; Werner, Winfried; Fürsich, Franz T.; Nützel, Alexander
Abstract: Protandrous sex change (sex change from male to female) is one of the diverse sexual expressions exhibited by bivalves, but its expression in the shell is quite rare. Previous studies on living and fossil astartids suggest a relationship between protandrous sex change and the formation of crenulations on the ventral shell margin at later ontogenetic stages. Here we report the formation of such crenulations in the Early Jurassic astartid Nicaniella rakoveci (Kuhn, 1935 ) from the Amaltheenton Formation at Buttenheim, Franconia. This is the earliest known record of protandrous hermaphroditism in fossil bivalves, predating previous reports by at least 13 Myr. A principal component analysis of linear size measurements and Fourier shape analysis of the shell outlines revealed that the outline of Nicaniella rakoveci specimens varies from subquadrate to subcircular, but this variation is independent of the presence or absence of crenulations and therefore not associated with sex. Crenulated specimens exhibit a lower height/inflation ratio than non-crenulated ones, suggesting that the protandrous females have more inflated valves than the males. The formation of crenulations was probably related to allocation of resources for reproduction. The most likely function of the crenulations was to increase the internal shell volume in the female stage to accommodate more eggs rather than being an adaptation against predation as often assumed for other bivalves. The formation of crenulations is part of the protandrous life history and probably is controlled by a genetic mechanism that is also responsible for sex change.